2020
DOI: 10.1038/s41598-020-61308-4
|View full text |Cite
|
Sign up to set email alerts
|

Retinal neurodegeneration in patients with end-stage renal disease assessed by spectral-domain optical coherence tomography

Abstract: Spectral-domain optical coherence tomography (SD-oct) represents a reliable tool for retinal layer volume and thickness measurement. the aim of this study was to evaluate retinal changes indicating neurodegenerative processes in patients with end-stage renal disease (eSRD) compared to healthy controls. This was a cross-sectional, single-center study comprising 32 ESRD patients and 38 controls. Sectoral retinal nerve fiber layer (RNFL) thickness and retinal layer volumes were obtained by SD-OCT. Age-and gender-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
1
9
0
3
Order By: Relevance
“…On the other hand, significantly decreased RNFLt was observed in CKD patients according to previous studies ( Demir et al, 2009 ; Jung et al, 2020 ; Wu et al, 2020 ). However, our study failed to detect significantly decreased RNFLt in either the CKD 1–2 group or the CKD 3–5 group compared to the control group.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…On the other hand, significantly decreased RNFLt was observed in CKD patients according to previous studies ( Demir et al, 2009 ; Jung et al, 2020 ; Wu et al, 2020 ). However, our study failed to detect significantly decreased RNFLt in either the CKD 1–2 group or the CKD 3–5 group compared to the control group.…”
Section: Discussionsupporting
confidence: 60%
“…However, the definition of CKD applied in the aforementioned studies was based on an eGFR of <60 ml/min/1.73 m 2 (CKD stages 3-5) and failed to include earlier stages CKD patients with an eGFR of > 60 ml/min/1.73 m 2 (namely, CKD stages 1-2) using parameters such as proteinuria or UACR to detect early renal damage and declining renal function. Our study evaluated retinal neural parameters in non-diabetic CKD patients of stages 1-2 (versus health subjects) and revealed that retinal neuronal impairment, which might even precede microvascular rarefaction and retinal axon damage, could be detected in earlier CKD stages than those reported in prior studies (Jung et al, 2020;Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although retinal neurodegeneration has been reported in prior studies [4][5][6], it is unclear to what extent it might cause visual acuity decline in CKD patients. Ganglion cell complex (GCC) thickness on spectral domain optical coherence tomography (OCT) is a sensitive biomarker for retinal ganglion cells (RGCs) loss and can be used as an indicator of the retinal neurodegeneration [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 93%
“…Patients with CKD could have increased risk of visual impairment by three-to seven-fold [2,3]. The causes of the visual decline may be attributed to either definite ocular diseases, such as cataract, glaucoma, age-related macular degeneration (AMD), diabetic retinopathy (DR), and other retinopathies [2,3], or non-specific ocular pathologies such as retinal microvascular degeneration and retinal neurodegeneration [4][5][6].…”
Section: Introductionmentioning
confidence: 99%